Massed and distributed practice on learning the forehand shot in tennis - Fuentes-García, J. P.; Pulido, S.; Morales, N.; Menayo, R. (International Journal of Sports Science & Coaching, 2022)
Purpose: This study aims to determine the effect of the distribution of practice on learning the forehand shot in tennis. Method: Twenty-four beginner tennis players participated in the study (13 males and 11 female; 8.63 ± 0.92 years old). The players were separated after groups -massed practice (N = 12) and distributed practice (N = 12). Each group practiced the forehand shot for 12 sessions, 4 series per session and 10 trials/series (6 weeks). The accuracy and efficacy were measured through one post-test and one retest, carried out 2 weeks after the last learning session.Results: Significant improvements in accuracy between the pre-test and post-test (p=.004) and between pre-test and re-test (p=.006) were found in the massed practice group. Significant improvements in accuracy between the pre-test and post-test (p=.002) and between pre-test and re-test (p=.001) were found in the distributed practice group. No significant differences were found between groups but there was a favourable trend toward better learning in both, with improved accuracy and efficacy.Conclusion: The motor learning through the distribution of practice among children has been noted, with a significant improvement in the skill acquisition of the forehand shot in the two groups. The results are useful because they clear up the doubts about how to plan the teaching of this stroke in tennis, confirming the suitability of carrying out learning programs based on massed and distributed practice.